Mediation In Criminal Articles According To The Algerian Legislation - Farid RAHAM (Akofena)
Abstract: Mediation in criminal matters is considered a successful alternative to criminal prosecution from the perspective of the Algerian legislator. This is due to its ability to achieve general objectives such as reducing the number of cases referred to trial judges, protecting the rights of the victim, and better fulfilling their claims compared to a judicial ruling. It also spares the accused from the negative consequences of prosecution, such as suspension from work, especially if they are employees. Therefore, the legislator has stipulated specific provisions for it, defining its formal and substantive conditions, outlining its procedural steps, and limiting its effects and scope to less serious crimes that primarily affect the rights of the victim.